Employees’ participation and commitment towards trade union functions and activities: A case study at Infineon Technology Sdn. Bhd. Batu Berendam Melaka / Mohd Shukri Mohd Shariff and Mohammad Rahmmat Hamid - Mohd Shariff, Mohd Shukri; Hamid, Mohammad Rahmmat (Faculty of Administrative Science and Policy Studies, 2012)
Nowadays, the existence of trade union in organization especially private organization is crucial in order to create balance harmonies relation between employee and employer. Trade union is functioning as association that protects the employee benefits and security. The decline in the participation towards trade union will give an effect towards the employer exploitation over the employee. The less amount of participation in the trade union make the trade union more weaken and powerless. This study was investigate the employee participation and commitment towards the trade union function and activities. In this research we are looking at the employee knoeledge about trade union, the important of trade union in employee view and the factor that contribute towards the employee particiapation and commitment towards trade union function and actiivites. We are looking at employment environmental reason, employee personal interest, trade union role and achievement and employee awareness as independant variable and individual participation and commitment as dependant variable. We are conducting the research in the most active trade union in malacca which is infineon technology sdn bhd with the sample size of 200 members of trade union. The result show there is no significant defferent perception between all independant variable. It also show that the function of trade union as a representative is the most significant factor towards the members of trade union. This study will help the trade union of the organization to increase their members participation and commitment towards the function and activities.